Sleep-Related Consequences of the COVID-19 Pandemic: A Survey Study on Insomnia and Sleep Apnea Among Affected Individuals - Hasan, Dler Osman; Aladdin, Aso Mohammed (Department of Public Health, Faculty of Health Sciences, Jenderal Soedirman University, 2024)
Background: The global outbreak of the COVID-19 pandemic, starting in December 2019, has profoundly disrupted people's well-being across the globe. Its impact extends far beyond physical health, reaching deep into our psychological well-being, potentially triggering sleep disorders like insomnia and sleep apnea. Numerous surveys are dedicated to assessing the impact of COVID-19 on sleep-related problems in individuals, whether during their infection or post-recovery. To achieve this objective, the study has amassed a wealth of data and insights based on rigorous scientific methods. Methods: The investigation evaluates and utilizes both insomnia severity index and the stop-bag method to ascertain the persisting presence of sleep issues after recuperation from COVID-19. The study collected data through an online and offline survey involving 403 participants who had contracted COVID-19 in Kurdistan Region of Iraq (KRI). For a clearer examination, data is analyzed using basic and advanced statistical methods. Results: Out of the participants, 195 (48.39%) had insomnia, 9 (2.23%) were at high risk for OSA, and 394 (97.77%) had low to moderate OSA risk. In the analysis, a statistically significant association was found: females (OR: 1.58, 95% CI: 1.02, 2.46, p = 0.0412) and those needing oxygen therapy (OR: 1.41, 95% CI: 10.66, 3.01, p = 0.3714) had a higher chance of experiencing insomnia. Conclusions: The study revealed a significant connection between psychological issues and factors like sleep duration, quality impairment, and increased sleep apnea risk among COVID-19 patients during and after their illness.